2019
DOI: 10.18619/2072-9146-2019-5-77-83
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characteristics of the biochemical composition of chard and table beet accessions from VIR collection

Abstract: Relevance. Healthy eating is one of the many steps that lead to a healthy nation. It implies the provision of the human body with all the necessary elements for its normal functioning. Within the framework of import substitution, it is extremely important to identify and popularize valuable crops that are suitable for cultivation in the territory of the Russian Federation. One of these rarely studied and insufficiently studied cultures is the leaf variety of beet –chard (Beta vulgaris L. ssp. сicla). Man uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…For example, corn protein lacks tryptophan, the contents of lysine and threonine in rice and wheat proteins have been found to be low, and the content of other essential amino acids in these cereals are also low. Amaranth protein is relatively rich in essential amino acids such as lysine and tryptophan, of which lysine is one of essential amino acids which other cereals lack (Sokolova et al, 2021). As such, it can be concluded that amaranth protein has superior functional characteristics in providing nutrition for people (Bressani & Garcia-Vela, 1990), and is one of the key reasons increased research interest into amaranth proteins.…”
Section: Specific Amino Acid Pattern Of Amaranth Proteinmentioning
confidence: 99%
“…For example, corn protein lacks tryptophan, the contents of lysine and threonine in rice and wheat proteins have been found to be low, and the content of other essential amino acids in these cereals are also low. Amaranth protein is relatively rich in essential amino acids such as lysine and tryptophan, of which lysine is one of essential amino acids which other cereals lack (Sokolova et al, 2021). As such, it can be concluded that amaranth protein has superior functional characteristics in providing nutrition for people (Bressani & Garcia-Vela, 1990), and is one of the key reasons increased research interest into amaranth proteins.…”
Section: Specific Amino Acid Pattern Of Amaranth Proteinmentioning
confidence: 99%
“…Libraries used in the process of analysis were NIST2010 (National Institute of Standards and Technology, USA), and the collections of standard compound mass spectra maintained by St. Petersburg State University and the Komarov Botanical Institute, with an affinity index no less than 80 (Shtark et al, 2019). Software used: UniChrom; AMDIS (Automated Mass Spectral Deconvolution and Identification System) (Sokolova et al, 2021).…”
Section: Biochemical Analysis Of Plant Accessionsmentioning
confidence: 99%